Financial Literacy, Digital Payment Adoption, and Trust in Advancing MSME Growth - Desta Maya, Zuna; Rahmawati, Yunaita (Journal Economic Business Innovation, 2025)
Purpose: This research aims to explore its core mechanisms of enterprise firm expansion by focusing on three natures-relational capitals, foundational managerial resources and technological adoption. It is distinct in that it examines the mediating impact of one important dynamic capability and the contextual effect of institutional support.Method: Research is a quantitative cross-sectional survey design. Results were obtained from data collected from a stratified sample of senior managers and analyzed with state-of-the-art statistical techniques, such as structural equation modeling and conditional process analysis for testing the hypothesized direct, mediating, or moderating relations.Findings: The findings indicate that financial skill, the adoption of digital financial instruments as well as strong personal relationships strongly facilitate growth. This effect is not direct and is completely mediated by the firm’s ability to be an agile entrepreneurship. In addition, public institutions exert positive moderating effects on these relationships, making the associations between core resources and strategic agility significant.Novelty: The research provides a new conceptual integrative model that explains the how and when of business growth. By going beyond contrived direct-effect models, we empirically identify a core dynamic capability as the key mediating process and institutional resources as an important boundary condition to offer insight into the functioning of strategic success.Implications: We offer actionable implications for managers: how they can strategically develop agility based on knowledge, technology and relational assets. For policy makers, the analysis highlights the need for institution and facilitative framework development to enhance the impact that firm-level resources generate towards competitive performance and economic resilience.